Field Acceptability of Improved Cotton Picking Bag on Drudgery Reduction of Farm Women (Indian Journal of Extension Education, 2016)
The present study was conducted in two villages viz., Dhanda Kheri and Dumerkhan of Jind District of Haryana state on purposively selected sample of 30 rural women respondents, who were actively involved in cotton picking. The respondents were demonstrated three types of cotton picking bags (cot-bag) viz traditional cloth and modified cot-bag. These two types of cot-bags were given to respondents for cotton picking and their responses towards each type of cot-bag were comparatively assessed on different parameters viz perceived health hazards or pain during cotton picking, impact of biomechanical, grip and physical stresses and tool factors and field acceptability. Each attribute was assessed with opinion of respondents as strongly agreed (S.A.), agreed (A) and disagreed (D). The data were collected by personally interviewing the respondents through a well structured interview schedule and were statistically analyzed.